2008
DOI: 10.17305/bjbms.2008.2994
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Hippuric Acid after Ingestion of Edible Fruits

Abstract: Aim of this study was to evaluate the biotransformation of simple phenols after ingestion of edible fruits and mixed food. It was analyzed hippuric acid in urine as biomarker of conjugation in the liver cells of glycine with aromatic phenolic acids such benzoic and salicylic acid from ingested food. Measurement of hippuric acid in urine samples of 10 healthy individuals: 5 female and 5 male with a mean age 51,5 years were recruited to participate in this study. Urine samples were collected for 24 hours. The ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
57
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(60 citation statements)
references
References 19 publications
2
57
1
Order By: Relevance
“…The PJ was less effective in terms of preventing lipid peroxidation in vivo, presumably due to the absence of polyphenolics such as anthocyanins and quercetin glycosides as well as their in vivo metabolites. Increased hippuric acid levels after supplementation with PJ are in accordance with results reported by others: the consumption of prunes (Toromanovic et al, 2008), green and black tea (Henning et al, 2013;Mulder, Rietveld, & van Amelsvoort, 2005), cider (DuPont et al, 2002), dried cranberry juice (Valentova et al, 2007), and lingonberries (Lehtonen et al, 2013) resulted in increased concentrations of hippuric acid, mainly in urine. The significant increase is most likely a direct consequence of the concentrations of typical hippuric acid precursors such as phenolic acids and other simple aromatic acids commonly more abundant in prunes and prune juice than in plum juice (Toromanovic et al, 2008).…”
Section: Parameterssupporting
confidence: 91%
See 1 more Smart Citation
“…The PJ was less effective in terms of preventing lipid peroxidation in vivo, presumably due to the absence of polyphenolics such as anthocyanins and quercetin glycosides as well as their in vivo metabolites. Increased hippuric acid levels after supplementation with PJ are in accordance with results reported by others: the consumption of prunes (Toromanovic et al, 2008), green and black tea (Henning et al, 2013;Mulder, Rietveld, & van Amelsvoort, 2005), cider (DuPont et al, 2002), dried cranberry juice (Valentova et al, 2007), and lingonberries (Lehtonen et al, 2013) resulted in increased concentrations of hippuric acid, mainly in urine. The significant increase is most likely a direct consequence of the concentrations of typical hippuric acid precursors such as phenolic acids and other simple aromatic acids commonly more abundant in prunes and prune juice than in plum juice (Toromanovic et al, 2008).…”
Section: Parameterssupporting
confidence: 91%
“…Increased hippuric acid levels after supplementation with PJ are in accordance with results reported by others: the consumption of prunes (Toromanovic et al, 2008), green and black tea (Henning et al, 2013;Mulder, Rietveld, & van Amelsvoort, 2005), cider (DuPont et al, 2002), dried cranberry juice (Valentova et al, 2007), and lingonberries (Lehtonen et al, 2013) resulted in increased concentrations of hippuric acid, mainly in urine. The significant increase is most likely a direct consequence of the concentrations of typical hippuric acid precursors such as phenolic acids and other simple aromatic acids commonly more abundant in prunes and prune juice than in plum juice (Toromanovic et al, 2008). Prior and colleagues investigated in healthy human subjects the metabolic fate of 5-hydroxymethyl-2-furfural (a typical component in dried plums/prune juice) following the consumption of prune juice and could identify several urinary glycine conjugates such as N-(5-hydroxymethyl-2-furoyl) glycine.…”
Section: Parameterssupporting
confidence: 91%
“…However, concentrations of the four phenolic acids decreased gradually after peaking at 30 min, indicating further chemical or microbial degradation of the phenolic compounds, as suggested by Keppler and Humpf (2005). The quantity of hippuric acid formed by biosynthesis is reported to directly correlate with the concentrations of its precursors, primarily phenolic acids (benzoic acid and salicylic acid) (Toromanovic et al, 2008).…”
Section: Discussionmentioning
confidence: 84%
“…However, nuclear magnetic resonance spectroscopic analysis of urinary HA in healthy children and adolescents (aged 7-18 y) (58) yielded mean HA values (311 mmol/mol creatinine) that were not substantially different from our data (393 and 319 mmol HA/mol creatinine for children and adolescents, respectively). One recent interventional study (14) also used the colorimetric method proposed by Tomokuni and Ogata (28) for HA measurements. In this study, the mean normal HA values [;1 g (5.58 mmol)/d] reported for 10 healthy, middle-aged adults exceeded the HA values found in our adolescent age group by .2-fold.…”
Section: Discussionmentioning
confidence: 99%
“…More recent human and animal studies [as well as older studies (10)] indicated increases in HA after the ingestion of several FV varieties, including blueberries (11), cranberries (10,12), apple products (13), cherries (14), black currants (15), and a mixed FV meal (16). The increases in HA seem to be mainly attributed to the metabolism of different dietary polyphenols (16) for which colored FV are a major food source.…”
Section: Introductionmentioning
confidence: 97%